Adaptation of the Kiswahili and Lingala Versions of the LittlEARS® Auditory Questionnaire (LEAQ) in Children with Normal Hearing in the Democratic Republic of Congo (DRC) - Ismael K. Byaruhanga; Frans Coninx; Karolin Schäfer (Audiology Research, 2025)
Background and objective: Currently, there is no universal newborn hearing (UNHS) screening in the Democratic Republic of Congo (DRC), partly due to financial and organizational reasons. The aim of this study was to adapt the LittlEARS® Auditory Questionnaire (LEAQ) into the Kiswahili and Lingala languages for use as a screening tool for auditory development in children less than two years of age, as objective hearing screening cannot be performed nationwide. Methods: For this purpose, norm data were collected from n = 723 infants (Lingala) and n = 648 infants (Kiswahili) aged between 0 and 24 months in a random selection of four out of seven health zones with pediatric services in the DRC. A non-linear regression model was derived for total scores by age. Pearson correlations were performed to determine whether there were differences between total scores of the questionnaire by region (urban/rural areas). A Mann–Whitney U-test was calculated to determine if there were differences depending on who completed the questionnaire (mother/other caregiver). In addition, a one-way ANOVA was used to determine whether there were differences in the total scores of the questionnaires according to the educational background of the person completing the questionnaire. Results: The Pearson correlation coefficient between total scores and age was 0.81 for Kiswahili and 0.77 for Lingala. There were no significant differences in total scores for all conditions tested (total scores by age, language, region, person who completed the questionnaire, educational background). Conclusions: The LEAQ can be used effectively in a large region such as the DRC, regardless of the region, respondent, and the educational background.